(untitled) (Innovative technologies, 2026)
The near-wellbore zone of reservoirs of various types is characterized by complex physical and chemical processes that determine well productivity and the efficiency of stimulation methods. This study examines three independent directions of near-wellbore transformation typical for oil and gas-condensate reservoirs of Uzbekistan. The first direction focuses on the influence of an electrical field on heavy-oil systems, where notable changes in rheological properties, threshold pressure, and filtration behavior are observed. The second direction is based on mathematical modeling of acid treatment in carbonate formations, incorporating dissolution kinetics, channel (wormhole) development dynamics, and the impact of geological heterogeneity on acid distribution. The third direction analyzes hydrochloric-acid technologies applied in low-pressure gas-condensate reservoirs, where mineralogical characteristics and reservoir fluid composition define specific mechanisms of rock–acid interaction.